Potential Use of Hexaflumuron Active Ingredient Bait and Fipronil Active Ingredient Spray in Controlling Termite Pests (Coptotermes curvignathus) in Palm Oil - AlKahfi, Rahmat; Hartini, Hartini; Nugraheni Sukmawati, Fitria (JURNAL AGRIMENT, 2024)
Soil termite control in oil palm plantations is currently focuses on spraying techniques on host plants. Spraying can kill termites on the surface of the trunk and damage their burrows, but because insecticides cannot penetrate the oil palm trunk, it cannot kill termites that nest in the trunk. The latest technology in subterranean termite control is the use of termite baits containing chitin synthesis inhibitor (CSls) components. The objective of this study was to determine the potential mortality of pest termites (Coptotermes curvignathus) in the field using baits containing the active ingredient hexaflumuron and sprays containing the active ingredient fipronil. This research was conducted on immature plants (TBM) at PT Mitra Agro Persada Abadi (MAPA) Central Kalimantan from December 2023 to January 2024. The research conducted showed that the results of the application of both baits containing the active ingredient hexaflumuron and sprays containing the active ingredient fipronil were effective against termite pests (Coptotermes curvignathus) in the form of termite extermination. However, sprays containing the active ingredient fipronil killed termites faster than commercial baits in terms of exposure time.